Avaliação das repercussões das ações do apoio pedagógico nas práticas docentes da educação superior do Uninta no estado do Ceará - Marques, Rita de Cássia Fortes (2023)
Teaching staff face a complex reality in Higher Education, in a context of teaching work to deal with diverse situations that require pedagogical innovations and the valorization of pedagogical practices from the perspective of praxis (action-reflection-transformed action). With the growth of undergraduate health courses in Higher Education Institutions (HEIs), there has been an increase in the demand for professionals who work in university teaching and a demand for higher quality teaching related to didactic-pedagogical issues, especially in the health area, which mostly has teachers with a bachelor's degree. The issues that emerge from the pedagogical management collective impose a preliminary dynamic for evaluating teaching work. The general aim of this thesis research is to evaluate the work of the Pedagogical Managers' Center (NUGESPE) in supporting the pedagogical managers of undergraduate health courses. We start from the principle that the best way to assess the impact on teaching of the implementation of NUGESPE is to establish a methodological study of descriptive and explanatory research, of a qualitative and quantitative nature in education, based on a Case Study, carried out at the INTA University Center - UNINTA. The results obtained from the application of 20 semi-structured interviews to teachers and a closed questionnaire to 18 educational managers are as follows: A) There is a need to make progress on some issues, such as improving communication and the speed with which information is shared, that the teachers understand the work of NUGESPE as pedagogical innovation, as a strategy for professional development at work (teacher professionalization / development of teacherliness; B) They understand the work of the pedagogical manager as a humanized approach, with great support and qualified listening that is relevant to the work of the teachers, as an initiative that represents a positive collaborative activity for the professional and organizational development of Centro Universitário Inta - UNINTA. It was therefore necessary to develop a virtual pedagogical platform for NUGESPE in order to improve and speed up pedagogical work and support for teachers, and to foster a culture of on-the-job training in the co-responsibility of the HEI.